Joyful Adventures and Frightening Places–Designing Emotion-Inducing Virtual Environments - Steinhaeusser, Sophia C.; Oberdörfer , Sebastian; von Mammen , Sebastian; Latoschik , Marc Erich; Lugrin , Birgit (Frontiers in Virtual Reality, 2022)
Virtual environments (VEs) can evoke and support emotions, as experienced when playing emotionally arousing games. We theoretically approach the design of fear and joy evoking VEs based on a literature review of empirical studies on virtual and real environments as well as video games' reviews and content analyses. We define the design space and identify central design elements that evoke specific positive and negative emotions. Based on that, we derive and present guidelines for emotion-inducing VE design with respect to design themes, colors and textures, and lighting configurations. To validate our guidelines in two user studies, we (1) expose participants to 360° videos of VEs designed following the individual guidelines and (2) immerse them in a neutral, positive and negative emotion-inducing VEs combining all respective guidelines in Virtual Reality. The results support our theoretically derived guidelines by revealing significant differences in terms of fear and joy induction.